Textured transparent conductive B/Al doped ZnO films utilizing reactive magnetron sputtering. Issue 113 (29th October 2015) - Liu, Yang; Huang, Qian; Bai, Lisha; Wei, Changchun; Zhang, Dekun; Zhang, Xiaodan
Abstract : Total transmittance ( T tot, solid line) and haze factor ( H T, dashed line) of the etched ZnO:B-320, ZnO:B/Al-450 and ZnO:Al films. Abstract : High-quality textured transparent conductive oxide (TCO) is significant to the exceptional performance of solar cells. In this study, textured B/Al doped ZnO (ZnO:B/Al) films were first reported utilizing reactive RF magnetron sputtering from an intrinsic ZnO ceramic target in a B2 H6 –Ar gas mixture. Elaborate thermal treatment was conducted for film optimization, as the temperature dependency of the B2 H6 source was quite sensitive. A compound structure with a 200 nm thick Al capping layer and 2000 nm thick ZnO:B main layer was proposed to further improve the annealing performance. The initial resistivity and mobility of the reactive sputtered ZnO:B/Al film were 4.8 × 10 −4 Ω cm and 32.1 cm 2 V −1 s −1 respectively. A remarkable surface texture with root-mean-square higher than 170 nm developed after a chemical etching procedure, resulting in average light scattering over 89% and total transmittance higher than 86% in the whole spectrum. These optical properties illustrate prominent progress in TCO application in thin film silicon (TFS) solar cells. Preliminary microcrystalline silicon solar cells deposited on textured ZnO:B/Al films indicate 0.6 mA cm −2 enhancement in short-circuit current density compared to conventional ZnO:Al front contacts, indicating potential application in high-efficiency TFS solar cells.